Rational Choice: The Contrast between Economics and Psychology - Smith, Vernon L. (Journal of Political Economy, 1991)
Rational Choice–the published record of a conference on economics and psychology–frames the issues as a contest between economic theory and the falsifying evidence from psychology. According to a third perspective, that of experimental economics, most standard theory provides a correct first approximation in predicting motivated behavior in laboratory experimental markets, but the theory is incomplete, particularly in articulating convergence processes in time and in ignoring decision cost. This view has roots in the work of Herbert Simon and Sidney Siegel, but it is not plainly represented in contemporary research in economic pyschology.